Thin-walled Integral Constructions in Aircraft Industry - Bałon, Paweł; Rejman, Edward; Świątoniowski, Andrzej; Kiełbasa, Bartłomiej; Smusz, Robert; Szostak, Janusz; Cieślik, Jacek; Kowalski, Łukasz (Procedia manufacturing, 2020)
Aviation structures are subjected to a wide spectrum of loads during operation. Each task carried out in flight consists of a number of maneuvers that generate different types of aircraft loading. Strict requirement for modern aviation constructions is high durability and reliability. This requirement means that many, sometimes contradictory restrictions, must be taken into account during the airplane design process. The most important element here is the mass of the structure having a decisive impact on both flight and technical properties as well as economic efficiency. This makes aircraft one of the most complex products of contemporary technology. Modern aviation constructions, or more precisely, their supporting structures are made almost exclusively as thin-walled structures that perfectly fulfill the postulate to minimize the weight of the construction. The structures are commonly used in which the cover is reinforced with longitudinal and transverse elements, providing the structure as a whole with the required rigidity and strength. While in the conditions of service load, local loss of coverage stability is permissible, exceeding the critical load levels of structural body components (frames, stringers) practically results in a structural damage. This specificity forces continuous improvement of both the design methods and the improvement of structural solutions for aircraft structures, as well as manufacturing processes, which is the subject of the project. The development of the science of materials, processing and machining processes as well as continuous improvement of technological processes has an impact on the effectiveness of these ideas. These disciplines allow the construction of geometrically complex integral structures that create opportunities not only for a more rational use of material characteristics, but also through appropriate shaping, significantly increase the mechanical properties of the support structure. An important advantage of the integral systems use is economic savings, gained as a result of elimination or reduction of assembly operations.This paper attempts to analyze the above-mentioned problem more closely, using the example of a densely ribbed rectangular plate.